Caracterização térmica de resíduos provenientes de usinas sucroalcooleiras para fins energéticos - Silva, Daniel Rodrigues da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents the study of the main wastes produced by sugarcane mills such as bagasse, filter cake and vinasse in addition to thermal characterization for energy generation. Bagasse is obtained after juice extraction in the mills. Filter cake is generated after clarification of the juice for sugar production and used as an additive in mineral fertilizers on the sugarcane crops. Vinasse is a by-product of ethanol production obtained after distillation and is also applied on the crops as a fertilizer and to restore water to the soil. The samples of bagasse, filter cake and vinasse were provided by two sugarcane mills located in the state of São Paulo. Chemical composition of samples was determined by several techniques like ultimate analysis, FTIR spectroscopy, X-ray diffractometry, atomic absorption spectrophotometry among others. Thermal decomposition behavior of both pure samples and binary blends (1:1 w/w) was evaluated by thermogravimetric analysis and its derivative (TGA-DTG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC). Typical reaction atmospheres of pyrolysis (N2), combustion (N2/O2, 8:2 v/v), oxy-combustion (CO2/O2, 8:2 v/v) and gasification (CO2) were employed. Thermal decomposition kinetics regarding the first mass loss step of degradation of organic matter was evaluated by Wanjun-Donghua method modified by Capela-Ribeiro. Results indicated that, despite similar organic composition, the energetic potential of filter cake and vinasse was lower than of bagasse due to increased inorganic content. Filter cake presented high amounts of Ca, Cu, Fe, Mn, P and Zn. Vinasse showed greater concentrations of Na and K and higher amounts of other metals such as Ca, Mg, Mn and Zn in relation to bagasse and filter cake samples. Both samples had significant concentrations of heavy metals like Cr and Pb. However, great differences were observed when chemical...

Esse trabalho apresenta o estudo dos principais resíduos da fabricação de açúcar e etanol a partir da cana-de-açúcar (o bagaço, a torta de filtro e a vinhaça) além da caracterização térmica dos mesmos para fins energéticos. O bagaço é obtido após a extração do caldo nas moendas. A torta de filtro é gerada no processo de clarificação do caldo na rota de produção do açúcar e utilizada na complementação da adubação mineral nos próprios canaviais. A vinhaça, também conhecida como vinhoto, restilo ou garapão, é um resíduo da fabricação de etanol após a etapa de destilação e também empregada como fertilizante, além de repor água ao solo. As amostras de bagaço, torta de filtro e vinhaça foram obtidas de duas usinas sucroalcooleiras do Estado de São Paulo. A caracterização química das amostras foi feita por diversas técnicas como análise elementar, espectroscopia vibracional na região do infravermelho (FTIR), difratometria de raios-X, espectrofotometria de absorção atômica, dentre outras. O comportamento de decomposição térmica, tanto das amostras individuais como de misturas binárias (1:1 m/m), foi avaliado através da análise termogravimétrica e sua derivada (TG-DTG), análise térmica diferencial (DTA) e calorimetria exploratória diferencial (DSC). As atmosferas empregadas foram de pirólise (N2), combustão (N2/O2, 8:2 v/v), oxi-combustão (CO2/O2, 8:2 v/v) e gaseificação (CO2). Foi avaliada a cinética de degradação térmica referente à primeira etapa de decomposição da matéria orgânica pelo método de Wanjun- Donghua modificado por Capela-Ribeiro. Os resultados obtidos demonstraram que, apesar de composição orgânica semelhante, o potencial energético da torta de filtro e da vinhaça foi inferior ao do bagaço devido ao alto teor de matéria inorgânica nas duas primeiras. A torta de filtro apresentou grandes quantidades de...
Keywords: Analise termica; Cana-de-açúcar; Bagaço de cana; Vinhaça; Cinetica quimica; Thermal analysis